Pengaruh TPACK (Technological, Pedagogical, and Content Knowledge) dan Kecerdasan Spiritual terhadap Kinerja Guru - Roby Setia Pramana; Marjoni Imamora; Muhammad Fazis; Annisaul Khairat (MANAZHIM, 2023)
This study aims to determine: 1) the effect of TPACK on teacher performance, 2) the effect of spiritual intelligence on teacher performance, and 3) the effect of TPACK and spiritual intelligence on teacher performance. This type of research is quantitative research with the Ex-Post Facto method. The population in this study were all teachers at SMA and MA Negeri in Payakumbuh, totaling 493 people. Sampling used a proportional stratified random sampling technique using the Slovin formula. The number of samples in this study were 221 teachers at all State Senior High Schools and State Senior High Schools in Payakumbuh City. The research instrument uses angles. The data collection technique in this study was carried out by distributing questionnaires using the Google form application and the link was shared via WhatsApp. Data analysis techniques were performed using multiple linear regression analysis. The results of the study show that: 1) there is an effect of TPACK on the performance of teachers in SMA and MA Negeri in Payakumbuh City. This is evidenced by the t-count value of the TPACK variable (X1) on teacher performance (Y) which is greater than the t-table (8,591 > 1,984), 2) there is an influence of spiritual intelligence on teacher performance at State Senior High Schools and State MAs in Payakumbuh City. This is evidenced by the t-count value of the spiritual intelligence variable (X2) on teacher performance (Y) which is greater than the t-table (6,487 > 1,984), 3) there is an influence between TPACK (and spiritual intelligence together on teacher performance in State Senior High Schools and State MAs in Payakumbuh City. This is evidenced by the value of the F-count analysis of the TPACK regression variable (X1) and spiritual intelligence (X2) on teacher performance (Y) which is greater than the F-table (260.079 > 3.00).